2014
DOI: 10.1161/circinterventions.113.000606
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Patients With Non–ST-Segment–Elevation Myocardial Infarction and Nonobstructive Coronary Artery Disease

Abstract: Background-Troponin elevation is a risk factor for mortality in patients with non-ST-segment-elevation acute coronary syndromes.However, the prognosis of patients with troponin elevation and nonobstructive coronary artery disease (CAD) is unknown. Our objective was therefore to evaluate the impact of nonobstructive CAD in patients with non-ST-segment-elevation acute coronary syndromes and troponin elevation enrolled in the Acute Catheterization and Urgent Intervention Triage Strategy (ACUITY) trial. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(77 citation statements)
references
References 27 publications
3
66
0
8
Order By: Relevance
“…They also had similar lengths of hospital stay, possibly as a result of further testing of MINOCA patients to enhance management. Prior studies have shown lower mortality with MINOCA (3.2–4.5%) than with MI‐CAD 3, 6, 7, 9. We observed lower mortality in VIRGO patients 5, 48, 49, 50.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…They also had similar lengths of hospital stay, possibly as a result of further testing of MINOCA patients to enhance management. Prior studies have shown lower mortality with MINOCA (3.2–4.5%) than with MI‐CAD 3, 6, 7, 9. We observed lower mortality in VIRGO patients 5, 48, 49, 50.…”
Section: Discussionsupporting
confidence: 41%
“…In contrast, patients with vasospasm more often reported recurrent angina, illicit drug use, and pregnancy‐related complications. With 1 in 10 young patients with AMI diagnosed with MINOCA,3, 4, 5, 6, 7, 8 our findings highlight both the challenges and the importance of pursuing a systematic approach to identify the underlying cause (coronary‐ischemic, non–coronary‐ischemic or nonischemic, or noncardiac) 13, 36…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A sizeable minority of patients with AMI are found to have MINOCA 3, 4, 5, 6, 7, 8, 9, 10, 11. Unfortunately, some physicians fail to realize that the absence of obstructive coronary arteries does not exclude the possibility of an AMI.…”
Section: Introductionmentioning
confidence: 99%
“…MINOCA is found in roughly 6% of AMI patients4; however, there is large variability in its reported prevalence, with a range of 3.5% to 15%,3, 4, 5, 6, 7, 8, 9, 10, 11 possibly attributable to differences in the studied populations and heterogeneity in its definition. MINOCA is also more common in younger patients and women 3, 4, 5, 6, 7.…”
Section: Introductionmentioning
confidence: 99%